Clockify and BOT Telegram Integration in Employee Performance Measurement Applications Development - Faisal Alfareza; Addin Aditya (School of Industrial and System Engineering, Telkom University, 2024)
Employee performance can go up and down without realizing it because of an understanding of theconcept of performance and concern for the achievement of underperformance. Poor performancedecreases productivity and if left unchecked, employees can be judged as not credible in carrying outtheir work. The Organization has not paid attention to these employee performance issues becausethere is no reporting system that allows employees to track the ups and downs of performance basedon their operations (productivity). The Clockify app as a daily operational tool cannot be used as abenchmark for performance improvement or decrease, so it does not offer any real motivation foremployees to gradually improve. Quantitative data analysis was carried out based on informantinterviews, employee observations of Clockify, and studies of Clockify output documents themselves.This research aims to identify the problem and develop a system to solve it. It is a system tocomplement Clockify's capabilities in visualizing employee performance and preventing continuousdecline due to unconsciousness. Build an employee productivity reporting system using Google AppsScript, Telegram Bot, and Clockify to present productivity reports in a graphical representationinstantly and systematically, helping employees see performance as an increase and decrease andpreventing continuous decline with a productivity analyzer service that calculates employeeproductivity based on a quantity of daily work that can be tracked and accounted for accuracy.